Наноструктурированные антидиффузионные слои в контактах к широкозонным полупроводникам - Кудрик Я.Я. (Технология и конструирование в электронной аппаратуре, 2013)
Исследована связь между антидиффузионными свойствами пленок на основе TiB₂ и их нанокристаллической структурой, определены оптимальные размеры нанокристаллитов и условия образования нанокристаллической пленки. Применение таких пленок в качестве антидиффузионных слоев в контактах к широкозонным полупроводникам позволяет повысить термостойкость приборов на их основе. Досліджено зв'язок між антидифузійними властивостями плівок TiB₂ та їх нанокристалічною структурою, визначено оптимальний розмір нанокристалітів та умови утворення нанокристалічної плівки. Застосування таких плівок як антидифузійних шарів в контактах до широкозонних напівпровідників дозволяє підвищити термостійкість приладів на їх основі. The interrelation between the antidiffusion properties of titanium diboride films and their nanocrystalline structure is investigated. We made a valid assumption that the main reason for degradation of contacts with TiB₂-based diffusion layers is diffusion through the TiB₂ film through dislocations (formed due to stresses that appear in the course of ohmic contact formation) rather than chemical interaction. In that case, increase of mechanical strength of the TiB₂ film at reduction of grain size will affect its diffusion strength more strongly than growth of diffusion penetrability owing to increase of grain boundary role. Our investigations showed that, to ensure maximal mechanical strength and heat stability, the size of nanocrystallites in films forming diffusion barriers has to lie within 3—15 nm. The TiB₂ films with optimal nanocrystallite parameters can be obtained using magnetron sputtering with discharge current of 0,4 A and oxygen content in a target up to 8 at.%. Application of TiB₂-based nanocrystal films as antidiffusion layers in contacts to wide-gap semiconductors makes it possible to raise heat stability of devices based on such semiconductors.